Oxygen isotope analyses of biogenic opal and quartz using a novel microfluorination technique. (15th July 2013) - Menicucci, Anthony J.; Matthews, Joy A.; Spero, Howard J.
Abstract : RATIONALE: Measuring δ 18 O values in silicates is difficult and hazardous in comparison with measurements of carbonate minerals due to the difficulty in breaking Si–O–Si bonds. A novel method for measurement of δ 18 O values from quartz and biogenic silica utilizing high‐temperature pyrolysis with continuous‐flow isotope ratio mass spectrometry (CF‐IRMS) is presented. METHODS: Samples were prepared by offline dehydroxylation/dehydration under vacuum at 1060°C. The dehydroxylated samples are mixed with polytetrafluoroethylene (PTFE) powder (2.3:1 PTFE/Si) and graphite in silver foil capsules and reacted in a vario PYRO cube TC/EA system in a glassy carbon reaction tube. Quartz and biogenic opal samples react with available carbon in a microfluorination environment upon decomposition of the PTFE, producing CO for analysis via CF‐IRMS. RESULTS: Silicate samples reacted quantitatively, producing data with yields ≥88% from ~400 µg samples. Multiple analyses with international standards demonstrated accuracy for replicate measurements (1σ range ±0.3–0.6‰), comparing favorably with previously published techniques. CONCLUSIONS: New data produced with the microfluorination technique are comparable with data from studies using existing methodologies. The microfluorination technique has the potential to greatly increase the number of laboratories producing silicate oxygen isotope data for mineralogic, paleoclimatic and biogeochemical applications. Copyright © 2013 John Wiley & Sons, Ltd.